Outcomes in patients with aggressive B‐cell non‐Hodgkin lymphoma after intensive frontline treatment failure. Issue 2 (30th September 2019) - Ayers, Emily C.; Li, Shaoying; Medeiros, L. Jeffrey; Bond, David A.; Maddocks, Kami J.; Torka, Pallawi; Mier Hicks, Angel; Curry, Madeira; Wagner‐Johnston, Nina D.; Karmali, Reem; Behdad, Amir; Fakhri, Bita; et al.
Abstract : Background: Salvage immunochemotherapy followed by high‐dose chemotherapy and autologous stem cell transplantation is the standard‐of‐care second‐line treatment for patients with relapsed/refractory diffuse large B‐cell lymphoma after first‐line R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone). Outcomes after receipt of second‐line immunochemotherapy in patients with aggressive B‐cell lymphomas who relapse or are refractory to intensive first‐line immunochemotherapy regimens (etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab [R‐EPOCH], rituximab, hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone alternating with methotrexate and cytarabine [R‐HyperCVAD], rituximab, cyclophosphamide, vincristine, doxorubicin, and high‐dose methotrexate alternating with ifosfamide, etoposide, and cytarabine [R‐CODOX‐M/IVAC]) remain unknown. Methods: Outcomes of patients with non‐Burkitt, aggressive B‐cell lymphomas and relapsed/refractory disease after first‐line treatment with intensive immunochemotherapy regimens who received platinum‐based second‐line immunochemotherapy were reviewed retrospectively. Analyses were performed to determine progression‐free survival (PFS) and overall survival (OS) from the time of receipt of second‐line immunochemotherapy. Results: In total, 195 patients from 19 academic centers were included in the study. The overall response rate to second‐line immunochemotherapy was 44%, with a median PFS of 3 months and a median OS of 8 months. Patients with early treatment failure (primary refractory or relapse <12 months from completion of first‐line therapy) experienced inferior median PFS (2.8 vs 23 months; P  < .001) and OS (6 months vs not reached; P  < .001) compared with patients with late treatment failure. Although the 17% of patients with early failure who achieved a complete response to second‐line immunochemotherapy experienced prolonged survival, this outcome could not be predicted by clinicopathologic features at the start of second‐line immunochemotherapy. Conclusions: Patients with early treatment failure after intensive first‐line immunochemotherapy experience poor outcomes after receiving standard second‐line immunochemotherapy. The use of standard‐of‐care or experimental therapies currently available in the third‐line setting and beyond should be investigated in the second‐line setting for these patients. Abstract : Patients with aggressive non‐Hodgkin lymphoma who fail intensive first‐line immunochemotherapy within 12 months experience poor outcomes with standard salvage immunochemotherapy. Standard‐of‐care and experimental therapies currently offered in the third‐line setting or later should be investigated earlier in this patient group.